Education Financing Model Transformation to Build Education Accessibility Through Free School Fees at PKBM Golden - Darmawan, Rina; Rugaiyah, Rugaiyah (Advances In Social Humanities Research, 2024)
The Ayo Lanjut Sekolah program at the Golden Community Learning Activity Center offers access to tuition-free education for those disconnected from the formal education system. This study explores the management of education financing in the program context. Through a literature review approach, this study identifies funding strategies from external sources and evaluates their impact on program sustainability. The findings show that this innovative approach successfully improves access to education without imposing costs on learners. The implication emphasizes the importance of alternative models in education financing management to support education inclusivity for equal access to education that can be widely accepted. Suggestions for future research include further development in the understanding of education finance management and mapping sustainable funding models for similar programs. This research is expected to provide valuable guidance for education practitioners in designing inclusive and sustainable financing strategies to ensure equitable access to education for all. The study utilized a literature review to assess education financing management strategies at the Golden Community Learning Activity Center, focusing on the impact of the Ayo Lanjut Sekolah Program. Results indicated that sourcing external funding, such as government grants and corporate donations, positively affected program sustainability. This innovative approach addresses financing challenges for marginalized communities, enhancing educational access. The findings underscore the significance of inclusive financing models in improving education accessibility for marginalized groups.